2023
DOI: 10.2147/prbm.s396702
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between College Students’ Belief in a Just World and Their Learning Satisfaction: The Chain Mediating Effects of Gratitude and Engagement

Abstract: Purpose This paper reveals the mechanism of the influence of belief in a just world on college students’ learning satisfaction, and provides reference for further improving the quality of talent training in higher education. Methods By convenient sampling method, 131,894 college students from 348 undergraduate universities in China were investigated on the belief in a just world scale, gratitude scale, learning engagement scale and learning satisfaction scale. Then, SPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Several studies have shown that there is a positive correlation between students' AS and their AA. For instance, Luo used a questionnaire to investigate a sample of 1158 college students [11]. The AS questionnaire consists of two dimensions: learning ability AS and learning behavior AS.…”
Section: Evidence From Empirical Studiesmentioning
confidence: 99%
“…Several studies have shown that there is a positive correlation between students' AS and their AA. For instance, Luo used a questionnaire to investigate a sample of 1158 college students [11]. The AS questionnaire consists of two dimensions: learning ability AS and learning behavior AS.…”
Section: Evidence From Empirical Studiesmentioning
confidence: 99%
“…This underscores the critical role that engagement plays in shaping students' academic experiences and performance. Studies such as those by Luo et al (2023) and Furo & Abbey (2020) have explored the relationship between learning engagement and academic achievement, highlighting the mediating role of engagement in influencing students' academic outcomes. The findings suggest that students who are more engaged in their learning process tend to achieve higher academic success, indicating a positive correlation between engagement and achievement.…”
Section: Synchronous and Asynchronous Learning Process: Academic Achi...mentioning
confidence: 99%
“…Currently, gratitude is an emotional trait of one individual who recognizes the kindness or help of the benefactor and tries to be rewarded [ 1 , 2 ]. Previous studies on gratitude focused more on college students [ 3 , 4 ] or special groups [ 5 , 6 ], and less on teenagers in general [ 7 ]. Moreover, adolescence is a critical period for cultivating and developing an individual’s gratitude [ 8 ].…”
Section: Introductionmentioning
confidence: 99%